Higher apprenticeship as educational strategy after the pandemic - Paolo Bertuletti; Andrea Potestio (Firenze University Press, 2021)
This article analyzes strengths and weaknesses of the higher apprenticeship programme carried out by the University of Bergamo within the bachelor's degree in educational sciences since the academic year 2017/2018. Starting from the voices of apprentices and tutors, a qualitative research tries to find out whether higher apprenticeship may be a good teaching strategy to enhance the principle of alternation between theory and practice in tertiary education.   L'apprendistato di terzo livello come strategia formativa per le società dopo il Covid.   L'articolo esplora punti di forza e criticità dei percorsi di apprendistato di terzo livello avviati dall'Università di Bergamo a partire dall'a.a. 2017/2018 nell'ambito del corso di laurea triennale in Scienze dell'educazione. La ricerca qualitativa consente, grazie alle testimonianze di apprendisti e tutor, di descrivere situazioni ed episodi di apprendimento e di mettere in evidenza come l'apprendistato di terzo livello, almeno potenzialmente, possa costituire un'ottima strategia didattica per realizzare il principio dell'alternanza formativa negli studi terziari.